2021
DOI: 10.54386/jam.v22i3.187
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perception and economic impact assessment of agromet advisory services in rainfed regions of Karnataka and Andhra Pradesh

Abstract: All India Coordinated Research Project on Agrometeorology (AICRPAM) of ICAR has started the micro-level Agromet Advisory Service (AAS) through its 25 cooperative centers across the country. Microlevel advisory based on weather forecast is the newer dimension of the AAS in the country. Studies on economic impact of these micro-level advisories are uncommon. Therefore, the present study was conducted using the field survey to assess the farmer’s perception and economic impact of micro-level AAS in Vijayapura and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The reason behind more preference for rainfall might be, rainfall plays a major role in each stage of crop production. The findings are in tune with Dupdal et al (2020).…”
Section: Preference Over Weather Parameterssupporting
confidence: 78%
“…The reason behind more preference for rainfall might be, rainfall plays a major role in each stage of crop production. The findings are in tune with Dupdal et al (2020).…”
Section: Preference Over Weather Parameterssupporting
confidence: 78%
“…S2). Dupdal et al 29 found that traditional farmers used 33% and 71% more herbicides and pesticides, respectively, compared to advisory-based management. Under WFBAS, the application of herbicides, pesticides and fungicides considers the relationship of different forecasted weather parameters such as temperature, rainfall and humidity with different stages of growth of rice.…”
Section: Discussionmentioning
confidence: 99%
“…S2). Dupdal et al 29 . found that traditional farmers used 33% and 71% more herbicides and pesticides, respectively, compared to advisory‐based management.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on farmer satisfaction have mainly concentrated on satisfaction with agricultural extension services (Elias et al, 2016;Kassem et al, 2021). Few published studies have investigated the overall satisfaction of farmers in adopting AAS (Dupdal et al, 2020;Arpitha et al, 2022). There is a significant gap in the research pertaining to satisfaction with various attributes of AAS.…”
Section: Review Of Literaturementioning
confidence: 99%